Efek Protektif Madu Hutan Terhadap Kerusakan Hepar Tikus Putih (Rattus novergicus) yang Diinduksi Etanol - Fairuz Quzwain; Armaidi Darmawan; Irga M (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRACT Background: Illegal alcohol is one of the big problems in Indonesia. The victims by drinking these kind of alcohols were found  in every place on this country every month. Alcohol gives the most harmful effect to the liver, its cells will die and become a scar. One of its effect is fatty liver. WHO recommends the using of traditional treatment for health community care, prevention of disease and disease treatment. One of the most well known traditional treatment is the using of honey. Objectives: The goal of this research is to know the protective effect of the forest honey to the white rat’s (Rattus norvegicus) damaged liver which is inducted by ethanol Methods: This experimental laboratory research used random controlled design method with the post test-only control group design pattern. The subjects of this research were 25 adult male white rats (Rattus norvegicus) Sprague Dawley strain which were divided in to five groups with 5 treatment groups. Result: The result of ANOVA test shows, there is a mean difference between those five treatment groups with p value = 0,000. Post-Hoc test shows, there is a mean difference between group 1 (normal control) with other four groups (p= 0,000), group 2 (pathologic control) and group 3 (dose I) with group 4 (dose II) and group 5 (dose III) (p=0,000). Conclusion: There is a protective effect of the forest honey to the white rat’s (Rattus norvegicus) damaged liver which is inducted by ethanol Key words: Ethanol, forest honey, fatty degenaration